Multisectoral actions of mental health during the COVID‐19 pandemic in Mazandaran province of Iran - Abdolkarim Ahmadi Livani; Farzad Gohardehi; Marzieh Azizi; Mahmoud Reza Hashemvarzi; Somayeh Taghavi; Sara Tonekaboni; Ramzanali Golchobi; Mehran Zarghami; Mohsen Aarabi; Forouzan Elyasi (Wiley, 2022)
Abstract Aim A widespread outbreak of COVID‐19 is followed by adverse effects on the mental health of the general population. Therefore, this study is an audit to investigate the activities of various organizations during the COVID‐19 pandemic in Mazandaran Province, Iran. Methods The aim of the study was to collect the data, the relevant officials in various organizations and units were contacted to collect the statistics of actions taken in psychology and psychiatry wards. Moreover, databases such as Google Scholar and Iranian resources were searched. Results According to the results, different healthcare systems worked in parallel during the peak of the COVID‐19 pandemic. For example, Mazandaran University of Medical Science [MAZUMS] Health Vice‐Chancellor performed the following activities during this crisis: establishing a virtual crisis management working group, holding a provincial educational committee to train the crisis management teams, organizing virtual psychological intervention teams in the healthcare systems, and so forth. In addition, the mental health activities by Mazandaran Welfare Organization during the COVID‐19 outbreak included providing hostelry free psychological counseling, quarantine boarding and rehabilitation centers, and providing harm prevention protocols of COVID‐19, especially for marginalized regions. In the third level of medical centers, including hospitals, consultation‐liaison psychiatry or psychiatrists and clinical psychologists, therapeutic interventions for comorbid psychiatric disorders with COVID‐19 disease, and online workshops for mental health were conducted to reduce burnout of medical staff and nurses. Conclusion This study can provide a good guideline for different service providers by using the experiences of other centers to achieve better results.